基于响应面法的丢手释放接头优化设计 - 万锋; 管锋; 王琼 (Jixie qiangdu)
In order to optimize the structural strength and weight of the release joint,a multi-objective optimization design method with stress and mass as objective functions was proposed.In this paper,the response surface methodology combined with finite element numerical analysis was used to construct the response surface model of stress and mass respectively with respect to structural parameters,and the interaction between the parameters was analyzed.Based on the response surface models,the optimal structural parameter configuration of the release joint was obtained by multi-objective optimization analysis.The stress of the optimized structure decreased by 19.5% with a slight increase in mass.Numerical and experimental verification shows that the optimized structure is safe and reliable.The proposed design method,which combines the response surface methodology,finite element numerical analysis and experimental testing,can provide reference for the design of similar mechanical or engineering structures.